INOVASI TRANSPORTASI RAMAH DIFABEL (STUDI KASUS KOMUNIKASI PEMASARAN TERPADU DIFABIKE INDONESIA DALAM EKSISTENSI BISNIS) - Nazila, Meli Firdausi (Fakultas Komunikasi dan Desain Program Studi Komunikasi dan Penyiaran Islam, 2025)
People with disabilities face discrimination in public facilities and employment. This has led to startups aimed at supporting them. Difabike Indonesia is a transportation service run by and for people with disabilities. As a new startup, it needs effective marketing strategies. This research investigates Difabike's integrated marketing communication. It uses the communication theory by Shimp & Andrews (2013) and employs a qualitative descriptive approach through case studies, including interviews, observations, and literature reviews. Data were analyzed following Miles, Huberman, and Saldana (2016) using collection, reduction, presentation, conclusion drawing, and verification. The study found that Difabike Indonesia uses various advertising methods, including brochures, vouchers, and online news. Their public relations involve event collaborations, social services, and entrepreneurship workshops. Sales promotions include free vouchers and fare subsidies. Online marketing is conducted via their website and social media, while personal selling is done through WhatsApp. Direct marketing involves partnerships with the Yogyakarta Cooperative and SME Service and Sibakul Markethub. The findings indicate that Difabike Indonesia's marketing communications are used, but they lack integration, particularly in social media promotion management.